Continuous Personal Dust Monitor Accuracy Testing 6/23/08 ? Introduction (The National Institute for Occupational Safety and Health (NIOSH), 2009)
New Continuous Personal Dust Monitors (CPDM) submitted to NIOSH for approval to sample coal mine dust must accurately measure respirable coal mine dust in mine environments. There are two steps in the process which may be done in any order. The manufacturer is required to submit the results of a comparative underground coal mine dust sampling study, where the candidate CPDM is compared to an approved coal mine dust sampling device (currently the Coal Mine Dust Personal Sampling Unit (CMDPSU)). This testing shall follow the guidelines outlined below and shall demonstrate through weighted regression analysis that the mean coefficient of variation with bias correction is equal to or less than 12.8%. The other step involves laboratory testing to determine the electronic and environmental stability. This testing must be conducted by a private, commercial, academic or other laboratory approved by NIOSH.